IDENTIFICATION OF A (1B)1R SUBSTITUTION AND 1BL.1RS TRANSLOCATION IN WINTER WHEAT INTROGRESSION LINES BY CYTOGENETIC AND MOLECULAR METHODS - I. I. Motsnyy; S. V. Chebotar; L. V. Sudarchuk; A. V. Galaev; Yu. M. Sivolap (Вавиловский журнал генетики и селекции)
The (1B) 1R wheat-rye chromosome substitution and 1BL.1RS translocation have been identified in original introgression stocks using cytological and molecular marker analysis. The pairing between short arms of chromosomes 1BL.1RS and bread wheat chromosome 1B is observed at a very low frequency (in 0,2–0,3 % of pollen mother cells). The translocation stocks are resistant to leaf and stem rusts, and the substitution stocks are susceptible because of the different origins of the chromosomes 1R involved in the translocation or substitution. The Hg1 gene for glume hairiness, inherited from cv. Hostianum 237, has been detected in some introgression stocks. Several stocks show hairiness on the leaf upper surface, lower surface and leaf margin. The character, probably originating from Ae. tauschii, was inherited from the synthetic wheat T. timopheevii Zhuk./Aegilops tauschii Coss.